2018
DOI: 10.1002/smi.2822
|View full text |Cite
|
Sign up to set email alerts
|

Savouring as a moderator of the combat exposure–mental health symptoms relationship

Abstract: Engaging in firefights or witnessing death and other types of combat experiences are occupational hazards associated with Post Traumatic Stress Disorder (PTSD) and depression in military personnel returning from combat deployments. The present study examined savouring beliefs as a moderator of the relationship between combat exposure and mental health symptoms among U.S. Army soldiers deployed to Operation Iraqi Freedom and Operation Enduring Freedom. Soldiers (N = 885) completed measures of combat exposure, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
2
7
0
1
Order By: Relevance
“…Research with older adults has also investigated the role of savoring in promoting resilience ( Smith and Hollinger-Smith, 2015 ) and positive attitudes toward aging ( Bryant et al, 2021 ), improving physical health ( Geiger et al, 2017 ), buffering the deleterious effects of illness on subjective well-being ( Smith and Bryant, 2016 ), and lowering cardiovascular reactivity and boosting agency ( Borelli et al, 2020 ). Savoring has also been identified as a resource in bereavement ( Permanadeli and Sundararajan, 2021 ), in lowering suicide risk ( Klibert et al, 2019 ), and in protecting soldiers from the psychological effects of combat exposure ( Sytine et al, 2018 ); and kill-joy thinking has been found to mediate the relationship between depression symptomatology and gambling disorder severity ( Rogier et al, 2019 ). In addition, researchers have used savoring to increase people’s consumption of healthy foods ( Coary and Poor, 2016 ), decrease overeating ( Black and Areni, 2016 ), and promote healthy relationships with food ( Batat et al, 2019 ).…”
Section: Historical Evolution Of the Concept And Measurement Of Savoringmentioning
confidence: 99%
“…Research with older adults has also investigated the role of savoring in promoting resilience ( Smith and Hollinger-Smith, 2015 ) and positive attitudes toward aging ( Bryant et al, 2021 ), improving physical health ( Geiger et al, 2017 ), buffering the deleterious effects of illness on subjective well-being ( Smith and Bryant, 2016 ), and lowering cardiovascular reactivity and boosting agency ( Borelli et al, 2020 ). Savoring has also been identified as a resource in bereavement ( Permanadeli and Sundararajan, 2021 ), in lowering suicide risk ( Klibert et al, 2019 ), and in protecting soldiers from the psychological effects of combat exposure ( Sytine et al, 2018 ); and kill-joy thinking has been found to mediate the relationship between depression symptomatology and gambling disorder severity ( Rogier et al, 2019 ). In addition, researchers have used savoring to increase people’s consumption of healthy foods ( Coary and Poor, 2016 ), decrease overeating ( Black and Areni, 2016 ), and promote healthy relationships with food ( Batat et al, 2019 ).…”
Section: Historical Evolution Of the Concept And Measurement Of Savoringmentioning
confidence: 99%
“…More recently, there has been increasing research on the important role savouring might play in the adjustment to a stressful life event. For example, the relationship between savouring capacity and better psychological adjustment is found in the context of stressful life events, such as negative life events in college life (Ford, Klibert, Tarantino, & Lamis, ), combat exposure (Sytine, Britt, Pury, & Rosopa, ), and stressful events in the couple life (Samios & Khatri, ). Further, neuroscience research supports the restorative function of reminiscing or recalling positive memories in the context of stress (Speer & Delgado, ).…”
Section: Introductionmentioning
confidence: 99%
“…Athletes may profit from similar types of brief interventions designed to help them make the most of positive experiences that have already taken place (i.e., reminiscing), that they are currently experiencing (i.e., savoring the moment), and that they expect to experience in the future (i.e., anticipating). Based on past savoring research (e.g., Doorley & Kashdan, 2021;Sytine et al, 2018), such savoring interventions could enhance athlete well-being by both enhancing ongoing positive emotional experiences, and by buffering the impact of negative events on negative emotional reactions. However, we should emphasize that research on savoring behavior among athletes is in its infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Savoring has been associated with greater feelings of happiness shortly after positive events (Jose et al, 2012), greater life satisfaction (Hurley & Kwon, 2013;, and lower levels of negative affect, stress, and depression (Bryant, 2003;Hurley & Kwon, 2012;Wilson et al, 2020). Savoring has also been shown to buffer the impact that negative life events have on negative emotional reactions and mental health symptoms (Sytine et al, 2018;2019). Despite these known benefits, little research has studied savoring among athletes.…”
Section: Savoring and Passionmentioning
confidence: 99%